Biomechanical evaluation of the Total Facet Arthroplasty System(®) (TFAS(®)): loading as compared to a rigid posterior instrumentation system - Sjovold, Simon G. (Springer-Verlag, 2012)
PURPOSE: To gain insight into a new technology, a novel facet arthroplasty device (TFAS) was compared to a rigid posterior fixation system (UCR). The axial and bending loads through the implants and at the bone-implant interfaces were evaluated using an ex vivo biomechanical study and matched finite element analysis. Kinematic behaviour has been reported for TFAS, but implant loads have not. Implant loads are important indicators of an implant’s performance and safety. The rigid posterior fixation system is used for comparison due to the extensive information available about these systems. METHODS: Unconstrained pure moments were applied to 13 L3–S1 cadaveric spine segments. Specimens were tested intact, following decompression, UCR fixation and TFAS implantation at L4–L5. UCR fixation was via standard pedicle screws and TFAS implantation was via PMMA-cemented transpedicular stems. Three-dimensional 10 Nm moments and a 600 N follower load were applied; L4–L5 disc pressures and implant loads were measured using a pressure sensor and strain gauges, respectively. A finite element model was used to calculate TFAS bone-implant interface loads. RESULTS: UCR experienced greater implant loads in extension (p < 0.004) and lateral bending (p < 0.02). Under flexion, TFAS was subject to greater implant moments (p < 0.04). At the bone-implant interface, flexion resulted in the smallest TFAS (average = 0.20 Nm) but greatest UCR (1.18 Nm) moment and axial rotation resulted in the greatest TFAS (3.10 Nm) and smallest UCR (0.40 Nm) moments. Disc pressures were similar to intact for TFAS but not for UCR (p < 0.04). CONCLUSIONS: These results are most applicable to the immediate post-operative period prior to remodelling of the bone-implant interface since the UCR and TFAS implants are intended for different service lives (UCR—until fusion, TFAS—indefinitely). TFAS reproduced intact-like anterior column load-sharing—as measured by disc pressure. The highest bone-implant moment of 3.1 Nm was measured in TFAS and for the same loading condition the UCR interface moment was considerably lower (0.4 Nm). For other loading conditions, the differences between TFAS and UCR were smaller, with the UCR sometimes having larger values and for others the TFAS was larger. The long-term physiological meaning of these findings is unknown and demonstrates the need for a better understanding of the relationship between spinal arthroplasty devices and the host tissue as development of next generation motion-preserving posterior devices that hope to more accurately replicate the natural functions of the native tissue continues.